Livelihoods as a key social determinant of malaria: Qualitative evidence from Uganda - Deane, Kevin; Atusingwize, Edwinah; Musoke, David (Taylor & Francis group, 2025)
Malaria continues to be one of the leading causes of morbidity and mortality in Africa. Recent progress towards eliminating malarias has stagnated and, in some cases began to reverse. One key dimension which remains poorly understood in malaria research is the social determinants of the disease, which direct attention to the conditions in which people live and work. We present findings from a qualitative study that explored perceptions and understanding of the social determinants of malaria in Uganda, one of the main endemic countries. We conducted 14 key informant interviews, 10 focus group discussions with community members, and 11 in-depth interviews with households recently impacted by malaria. Our participants identified livelihoods and related practices as important social determinants. These included engaging in crop production with a focus on maize cultivation, livestock husbandry, construction, a range of activities conducted at dusk/night, and the gendered nature of specific livelihoods. The precise mechanisms noted through which these livelihood activities were related to malaria include increasing exposure to mosquitoes at dusk/night, the creation of new mosquito breeding sites, attracting mosquitoes to housing, providing feeding sites for mosquitoes, working near mosquito breeding sites, and the role that gendered care responsibilities play in exposing children to mosquitoes. Our findings emphasize the importance of engaging in these livelihood activities, given that they are widespread in Uganda and other African countries. We recommend that malaria prevention be incorporated into socio-economic development strategies, and urge researchers, policy makers, practitioners and other stakeholders to engage with the social determinants of malaria. International Bibliography of the Social Sciences (IBSS)
Keywords: Malaria; social determinants; livelihoods; agriculture; Uganda